Everyday Computing with Windows 8.1 - Wilson, Kevin (Springer, 2015)
Get the most out of Windows 8.1 for your every day computing tasks, with no jargon. Clear, concise and to the point. This brief book, Everyday Computing With Windows 8.1 provides the essentials of using a desktop or laptop running Windows 8 or 8.1, providing a fast read for the beginner and the enthusiast. Windows 8 can give new users fits with options that are well hidden; this book uncovers those so that the user can be relieved of frustration.